Early watermills: an archaeological indication of taxation? - Jessen, Mads Dengsø (Danish Journal of Archaeology, 2017)
The introduction of watermills in Southern Scandinavia has often been linked to the advent of the Cistercian Order and regarded a kick-starter for the so-called medieval revolution. In the present article, the archaeological evidence for watermills predating the religious order will be investigated and an earlier and alternative origin laid out. Here, the increased specialisation and centralisation pertaining to the Late Iron Age and Viking Age will be introduced as a significant cause for the initial construction of watermills, and the extensive excavations at Viking Age Omgaard, Denmark, will figure as case in point. Also, essential social mechanisms such as taxation and elite privileges will be highlighted as overlooked triggers in the Viking Age employment of watermills.